Virtual reality to characterize anticipation skills of top-level 4 x 100 m relay athletes - Chomienne, L.; Egiziano, M.; Stefanuto, L.; Bossard, M.; Verhulst, E.; Kulpa, R.; Mascret, N.; Montagne, G. (European Journal of Sport Science, 2024)
One marker of expertise in sport is athletes' ability to anticipate future events. In the 4 × 100 m relay, these anticipation skills are an essential asset for initiating their run at the right time. However, no study has focused on describing the underlying perceptual-motor processes involved. Virtual reality provides powerful tools to describe and understand these processes, overcoming the drastic constraints encountered in the real world. Nineteen athletes from the French national teams were immersed in a digital replica of the Stade de France and confronted with digital twins of potential partners based on motion capture. Their task was to initiate their run exactly when their virtual partner passed over a go-mark placed on the ground. The timing of different body motor events and visual behavior were measured and analyzed. Results showed that the execution of this highly constrained task is the result of a significant reduction in the variability of motor events preceding the start. These findings reveal the implementation of a perceptual-motor dialog until the initiation of the run. This study is a first step toward understanding the mechanisms underlying anticipation skills in the 4 × 100 m relay; it constitutes a preliminary step to the deployment of VR training protocols.